The Military Cooperation Between Türkiye and Somalia Under the AK Party - ELMI, BUREKA HASSAN (İstanbul Kültür Üniversitesi, 2025)
This study examines the evolution of military cooperation between Türkiye and Somalia under the leadership of the Justice and Development Party (AK Party), applying the theoretical lens of Foreign Policy Analysis (FPA). It investigates how Türkiye's Africa Opening Policy, initially rooted in humanitarian outreach, transitioned into a broader strategic engagement positioning Somalia as its most prominent partner in the Horn of Africa. The thesis explores key drivers behind this transformation, including Türkiye's aspiration for regional influence, Somalia's strategic maritime location, and the AK Party's ideology-driven foreign policy vision. The research adopts a qualitative case study approach, focusing on significant developments such as the establishment of Camp TURKSOM, bilateral military training programs, and diplomatic initiatives like the 2024 Ankara Declaration. The analysis argues that Türkiye's approach reflects a hybrid foreign policy model blending military (hard) power with humanitarian aid, development cooperation, and religious-cultural diplomacy (soft power). Meanwhile, Somalia utilizes this asymmetric partnership to rebuild its national army, enhance governance capacity, and balance competing external influences, especially from Gulf States. The study contributes to broader international relations discourse by illustrating how rising powers engage with fragile states through multidimensional diplomacy. It also highlights the durability and risks of such partnerships in the context of regional instability and political transitions.
Keywords: Türkiye; Somalia; Foreign Policy Analysis; AK Party; Camp TURKSOM